Faculty members' understanding on constructivist approach - Celikoz, Mine; Celikoz, Nadir (DEOMED PUBL, ISTANBUL, 2016)
The purpose of this study was to define the understanding (s) of constructivism held by faculty members in the field of curriculum and instruction departments. The qualitative research design was employed, within a phenomenological approach for this study. The criterion and conveniences sampling techniques were combined and the opinions of nine faculty members employed at different universities in Turkey were elicited. The data were obtained in the spring of 2015 through via a semi-structured interview form. The data were analyzed via a content-analysis method and the following five themes were created: relativity, skepticism, learner-centeredness, multiculturalism and world citizenship. Findings of this study was also obtained from the study and it was concluded that while certain participants regarded constructivism as merely a learning concept, other participants perceived it as both a learning theory and an educational philosophy. It was observed that participants were in agreement that knowledge was relative, and that there was a need to approach knowledge with doubt and to move the student place the student at the center of the educational process. Moreover, the conclusion was reached that certain participants, within their understanding of constructivism, did not allocate space incorporate the concepts of multiculturalism or world citizenship or did not associate these with the issue of constructivism. Furthermore, it may be concluded that although certain participants expressed their reservations (with regard to particular issues), all participants had indeed embraced the fundamental principles of multiculturalism and world citizenship.
Keywords: Constructivism; faculty members; phenomenological design; qualitative research; KNOWLEDGE; EDUCATION; TEACHERS; BELIEFS; Education & Educational Research